Environmental parameters and management as factors affecting greenhouse gas emissions from clay soil - Kristine Valujeva; Jovita Pilecka-Ulcugaceva; Madara Darguza; Kristaps Siltumens; Ainis Lagzdins; Inga Grinfelde (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science)
Greenhouse gas emissions (GHG) drive climate change, with agricultural land significantly contributing, influenced by soil properties. While extensive research exists on environmental and management impacts on GHG emissions across various soils and climates, understanding key factors influencing GHG emissions from clay soil in temperate climates is limited. This study aims to investigate the combination of environmental and management factors reducing N2O, CO2, and CH4 emissions from clay soil in temperate climates. Recognising the potential of reduced tillage and legume-based crop rotations in mitigating GHG emissions, we investigate their impact on soil emissions. The conventionally managed field with spring barley, field beans, winter wheat, and winter rapeseed rotation demonstrates the lowest average N2O emission (3.7 g N2O ha−1 d−1), while the field with winter crops in a reduced tillage rotation shows the highest N2O emission (8.5 g N2O ha−1 d−1). A rotation with winter crops, beans twice, and barley, under conventional management, demonstrates the highest CO2 emission (140.2 kg CO2 ha−1 d−1), while the lowest CO2 emission is observed in a rotation with winter crops, beans, and barley under reduced tillage management (100.8 kg CO2 ha−1 d−1). CH4 assimilation ranges from 3.1 to 5.4 CH4 g ha−1 d−1 across all rotation and tillage combinations. However, ANCOVA results indicate that the volumes of GHG emissions are significantly influenced by the interaction of environmental and management factors, where precipitation is the most significant factor in the interaction with other environmental factors, soil tillage, and crop residues for N2O and CO2 emissions, while CH4 emissions are influenced by the interaction of air temperature with other environmental factors, soil tillage, and crop residues. This underscores the need to consider both management and relevant environmental factors when evaluating the impact of practices on GHG emissions from clay soil in temperate climates.